ZNF692 promotes osteosarcoma cell proliferation, migration, and invasion through TNK2-mediated activation of the MEK/ERK pathway - Di Zheng; Zhun Wei; Chong Zhang; Wenda Liu; Changtian Gong; Fei Wu; Weichun Guo (Biology Direct, 2024)
Abstract Background Osteosarcoma is a diverse and aggressive bone tumor. Driver genes regulating osteosarcoma initiation and progression remains incompletely defined. Zinc finger protein 692 (ZNF692), a kind of Krüppel C2H2 zinc finger transcription factor, exhibited abnormal expression in different types of malignancies and showed a correlation with the clinical prognosis of patients as well as the aggressive characteristics of cancer cells. Nevertheless, its specific role in osteosarcoma is still not well understood. Methods We investigated the dysregulation and clinical significance of ZNF692 in osteosarcoma through bioinformatic method and experimental validation. A range of in vitro assays, including CCK-8, colony formation, EdU incorporation, wound healing, and transwell invasion tests, were conducted to assess the impact of ZNF692 on cell proliferation, migration, and invasion in osteosarcoma. A xenograft mouse model was established to evaluate the effect of ZNF692 on tumor growth in vivo. Western blot assay was used to measure the protein levels of MEK1/2, P-MEK1/2, ERK1/2, and P-ERK1/2 in cells that had been genetically modified to either reduce or increase the expression of ZNF692. The relationship between ZNF692 and tyrosine kinase non-receptor 2 (TNK2) were validated by qRT-PCR, chromatin immunoprecipitation and luciferase reporter assays. Results Expression of ZNF692 was increased in both human osteosarcoma tissues and cell lines. Furthermore, the expression of ZNF692 served as an independent predictive biomarker in osteosarcoma. The results of the survival analysis indicated that increased expression of ZNF692 was associated with worse outcome. Downregulation of ZNF692 inhibits the proliferation, migration, and invasion of osteosarcoma cells, whereas upregulation of ZNF692 has the opposite impact. Western blot assay indicates that reducing ZNF692 decreases phosphorylation of MEK1/2 and ERK1/2, whereas increasing ZNF692 expression enhances their phosphorylation. U0126, a potent inhibitor specifically targeting the MEK/ERK signaling pathway, partially counteracts the impact of ZNF692 overexpression on the proliferation, migration, and invasion of osteosarcoma cells. In addition, ZNF692 specifically interacts with the promoter region of TNK2 and stimulates the transcription of TNK2 in osteosarcoma cells. Forcing the expression of TNK2 weakens the inhibitory impact of ZNF692 knockdown on P-MEK1/2 and P-ERK1/2. Similarly, partly inhibiting TNK2 counteracts the enhancing impact of ZNF692 overexpression on the phosphorylation of MEK1/2 and ERK1/2. Functional tests demonstrate that the suppressive effects of ZNF692 knockdown on cell proliferation, migration, and invasion are greatly reduced when TNK2 is overexpressed. In contrast, the reduction of TNK2 hinders the ability of ZNF692 overexpression to enhance cell proliferation, migration, and invasion. Conclusion ZNF692 promotes the proliferation, migration, and invasion of osteosarcoma cells via the TNK2-dependent stimulation of the MEK/ERK signaling pathway. The ZNF692-TNK2 axis might potentially function as a possible predictive biomarker and a promising target for novel therapeutics in osteosarcoma.